Towards an Ethical Framework Grounded in Everyday Business Life (Issues in Social and Environmental Accounting (ISEA), 2007)
Business is increasingly concerned to reconcile investor driven pressure to perform with state driven pressure to conform (to a cascade of new regulation). Ethics generally favors the latter at the expense of the former. The ethical frameworks developed in the last few years differ from their classical predecessors, however. Integrative Social Contract Theory begins with the business contract and moves out from there to the wider society. Care theory begins with the relationship between two individual persons and moves out from there. Both theories are skeptical of the Universalist claims of classical ethical and religious frameworks and both claim to be user friendly. This paper compares and contrasts the two theories and hopes to show how the ethical lacunae in ISCT can be fixed by Care Theory. How a business would operate under the sway of Care Theory is described. Fears that Care Theory cannot be applied to business without weakening competitive strength are addressed. The paper is offered as a step towards merging ISCT and Care Theory to evolve an ethical framework for business. It would be a framework that engages fully with business realities, especially competitive realities, but that is directly and clearly guided by classical ethical principles.